Bye, bye, butterflies! - Larsen, Andrew, 1960- (Tell-me-more storybook., 2012)
Inspired by the sight of some school kids releasing butterflies up into the sky, a young boy turns into a "butterfly scientist" and helps his teacher and classmates care fro some caterpillars as they grow into butterflies.